Sedation and analgesia practices in neonatal intensive care units (EUROPAIN): results from a prospective cohort study. Issue 10 (October 2015) - Carbajal, Ricardo; Eriksson, Mats; Courtois, Emilie; Boyle, Elaine; Avila-Alvarez, Alejandro; Andersen, Randi Dovland; Sarafidis, Kosmas; Polkki, Tarja; Matos, Cristina; Lago, Paola; Papadouri, Thalia; Montalto, Simon Attard; et al.
Summary: Background: Neonates who are in pain or are stressed during care in the intensive care unit (ICU) are often given sedation or analgesia. We investigated the current use of sedation or analgesia in neonatal ICUs (NICUs) in European countries. Methods: EUROPAIN (EUROpean Pain Audit In Neonates) was a prospective cohort study of the management of sedation and analgesia in patients in NICUs. All neonates admitted to NICUs during 1 month were included in this study. Data on demographics, methods of respiration, use of continuous or intermittent sedation, analgesia, or neuromuscular blockers, pain assessments, and drug withdrawal syndromes were gathered during the first 28 days of admission to NICUs. Multivariable linear regression models and propensity scores were used to assess the association between duration of tracheal ventilation (TV) and exposure to opioids, sedatives-hypnotics, or general anaesthetics in neonates (O-SH-GA). This study is registered with ClinicalTrials.gov, number NCT01694745 . Findings: From Oct 1, 2012, to June 30, 2013, 6680 neonates were enrolled in 243 NICUs in 18 European countries. Mean gestational age of these neonates was 35·0 weeks (SD 4·6) and birthweight was 2384 g (1007). 2142 (32%) neonates were given TV, 1496 (22%) non-invasive ventilation (NIV), and 3042 (46%) were kept on spontaneous ventilation (SV). 1746 (82%), 266 (18%), and 282 (9%) neonates in the TV, NIV, and SV groups, respectively, were given sedation or analgesia as a continuous infusion, intermittent doses, or both (p<0·0001). In the participating NICUs, the median use of sedation or analgesia was 89·3% (70·0–100) for neonates in the TV group. Opioids were given to 1764 (26%) of 6680 neonates and to 1589 (74%) of 2142 neonates in the TV group. Midazolam was given to 576 (9%) of 6680 neonates and 536 (25%) neonates of 2142 neonates in the TV group. 542 (25%) neonates in the TV group were given neuromuscular blockers, which were administered as continuous infusions to 146 (7%) of these neonates. Pain assessments were recorded in 1250 (58%) of 2138, 672 (45%) of 1493, and 916 (30%) of 3017 neonates in the TV, NIV, and SV groups, respectively (p<0·0001). In the univariate analysis, neonates given O-SH-GA in the TV group needed a longer duration of TV than did those who were not given O-SH-GA (mean 136·2 h [SD 173·1] vs 39·8 h [94·7] h; p<0·0001). Multivariable and propensity score analyses confirmed this association (p<0·0001). Interpretation: Wide variations in sedation and analgesia practices occur between NICUs and countries. Widespread use of O-SH-GA in intubated neonates might prolong their need for mechanical ventilation, but further research is needed to investigate the therapeutic and adverse effects of O-SH-GA in neonates, and to develop new and safe approaches for sedation and analgesia. Funding: European Community's Seventh Framework Programme.